2012
DOI: 10.1902/jop.2011.110392
|View full text |Cite
|
Sign up to set email alerts
|

Oral Mucosa Tissue Response to Titanium Cover Screws

Abstract: The biologic effects seen in the mucosa in contact with the cover screws might be associated with the presence of titanium or other elements, such as aluminum or vanadium. The potential long-term biologic effects of particles on soft tissues adjacent to metallic devices should be further investigated because these effects might affect the clinical outcome of the implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
71
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 42 publications
14
71
0
6
Order By: Relevance
“…Under normal conditions, the gingival tissue is composed of healthy oral epithelium and connective tissue along with varying percentages of inflammatory cells. Based on the results of the present study at all evaluated tissue levels, the presence of small (<10 mm) and large (>30 mm) metallic particles was confirmed, consistent with the results of the studies by Flatebo et al [10] and Olmedo et al, [8] indicating signs of release of metals from implants into the gingival tissues overlying the implants in a large number of patients. One of the concerns in relation to dental implants is the local corrosion of the cover screw components into its overlying soft tissues and the possible complications, such as induction of allergic and inflammatory reactions, or the premature exposure of the implant into the oral cavity.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Under normal conditions, the gingival tissue is composed of healthy oral epithelium and connective tissue along with varying percentages of inflammatory cells. Based on the results of the present study at all evaluated tissue levels, the presence of small (<10 mm) and large (>30 mm) metallic particles was confirmed, consistent with the results of the studies by Flatebo et al [10] and Olmedo et al, [8] indicating signs of release of metals from implants into the gingival tissues overlying the implants in a large number of patients. One of the concerns in relation to dental implants is the local corrosion of the cover screw components into its overlying soft tissues and the possible complications, such as induction of allergic and inflammatory reactions, or the premature exposure of the implant into the oral cavity.…”
Section: Resultssupporting
confidence: 92%
“…In the studies carried out by Flatebo et al [10] and Olmedo et al, [8] the connective tissue adjacent to the cover screw exhibited a maximum number of metallic particles. In this study, the presence of metallic particles with different sizes in the most superficial layer of the soft tissue overlying the cover screw indicated that the corrosion of the components of the cover screw was not confined to the contact area of the overlying connective tissue.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In this context, 153 patients rehabilitated with single implants underwent biopsy of the mucosa adjacent to the implant cover screws during the period of osseointegration (4–6 months). In total, 41% of these patients showed Ti particles released from the implant surface, sometimes free or surrounded by macrophages, denoting foreign body reaction with probable metal corrosion [30].…”
Section: Introductionmentioning
confidence: 99%